(untitled) (Jurnal Bahasa, 2009)
The essence of the theory of accommodation lies in the social psychological research on similarity-attraction. The study suggests that an individual will try to influence the other individual by reducing the dissimilarties gap. Accommodation process operates on this principle and reflects the individuals desire for social approval. The research indicates that language accommodation is a dominant aspect in the interaction between Malay-Chinese community. The work focusses on verbal language during an interaction. Language accommodation helps individual to understand another individual through speech, behaviourial interpretation according to needs, situations and also seeking ways to avoid conflict to ensure smooth communication process. Malay is the chosen language among users even though code mixing and colloquial do exist. What is important is that accommodation process helps them to communicate in a multiracial society such as in Malaysia.